Токсикологическое изучение кумазида - Белоусов М. В. Михаил Валерьевич; Новожеева Т. П.; Ахмеджанов Р. Р. Рафик Равильевич; Новицкая Л. Н.; Юсубов М. С. Мехман Сулейман-оглы (Сулейманович); Аминин Д. Л.; Авилов С. А.; Стоник В. А.; Калинин В. И. (2010, 2010)
Заглавие с экрана